Critiquing Sustainable Openness in Technology-Based Education from the Perspective of Cost-Effectiveness and Accessibility - Junhong Xiao (Open Praxis, 2023)
The over-exaggeration of technology’s role in education has dominated the landscape of research, often resulting in the negligence of other important issues. This article critiques openness in technology-based education from the perspective of sustainability, put more specifically, cost-effectiveness and accessibility, both of which have direct impact on sustainable openness. It first reviews the purpose of using technology in education advocated in strategy documents, namely using technology to break the iron triangle of access, cost, and quality, hence increasing openness in high-quality education. It contends that technology-based education cannot be sustainably open without both cost-effectiveness and accessibility. Nevertheless, sustainable openness is an under-researched theme according to the findings from a review of 3,059 primary studies conducted in this article. The article then goes on to rethink sustainable openness in the digital age, arguing that technology-based education should be cost-effective to educational institutions and students alike and cater for socio-economic diversity and disparity, among other things, to ensure sustainable openness to all. It concludes by calling for a critical approach to researching technology-based education with the aim of achieving high quality, cost-effectiveness, and accessibility at the same time and opening up education to all.